1990
DOI: 10.1071/rd9900683
|View full text |Cite
|
Sign up to set email alerts
|

Developmental capacity of mechanically bisected mouse morulae and blastocysts

Abstract: Mouse embryos were mechanically bisected at the morula, early blastocyst or expanded blastocyst stages of development and cultured in vitro to the expanded blastocyst stage. Their capacity for postimplantation development was assessed after transfer to pseudopregnant foster mice. Embryos bisected at blastocyst stages had a higher survival rate in vitro than those bisected at the morula stage. Half-embryos had approximately half the number of cells at the blastocyst stage as control embryos, but the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Reduction in ICM and trophoblast cells may affect implantation and development (Chan et al, 2000;Modlinski et al, 2002). Failure to form a fetus may be due to the absence of egg cylinder development, which is correlated with the reduced number of the ICM cells (Wang et al, 1990). Failure to form a fetus may be due to the absence of egg cylinder development, which is correlated with the reduced number of the ICM cells (Wang et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in ICM and trophoblast cells may affect implantation and development (Chan et al, 2000;Modlinski et al, 2002). Failure to form a fetus may be due to the absence of egg cylinder development, which is correlated with the reduced number of the ICM cells (Wang et al, 1990). Failure to form a fetus may be due to the absence of egg cylinder development, which is correlated with the reduced number of the ICM cells (Wang et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This was ascribed to the diminution of cell numbers in the ICM due to the bisection procedure. Consequently, the embryos failed in the egg-cylinder formation (Wang et al, 1990).…”
Section: Stage Of Embryo Bisection Matters: Lessons From Sheep Cattlmentioning
confidence: 99%
“…In sheep, it was also shown to be beneficial to twin embryo development if the embryos were transferred to recipients that had more than one ovulation during the estrus of transfer (Szell and Hudson, 1991). Monozygotic twin blastocysts generated by bisection of mouse embryos in the blastocyst stage revealed that it is not only important to have synchrony in estruses, but also to provide extra time for the embryo to propagate its cells in an in vivo environment before implanting to the uterus (Wang et al, 1990).…”
Section: Challenges Pending and Requirements Of Experimental Monozygomentioning
confidence: 99%
“…Finally, assuming the trophectoderm is sufficient, adequate function of the inner cell mass is also essential to provide the body of the embryo. A critical mass of functional cells will be required to form a viable fetus (mice: Wang et al, 1990); failure to form the critical mass of cells may result in early pregnancy loss or an anembryonic pregnancy. The development of a blood circulation within the fetus relies upon mesoderm formation and this is key for survival of the early post-implantation mouse embryo (Copp, 1995).…”
Section: A Sliding Scale Of Developmental Viability Checks?mentioning
confidence: 99%